2013
DOI: 10.3402/gha.v6i0.18619
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with job satisfaction among commune health workers: implications for human resource policies

Abstract: BackgroundJob satisfaction among health workers is an important indicator in assessing the performance and efficiency of health services.ObjectiveThis study measured job satisfaction and determined associated factors among health workers in 38 commune health stations in an urban district and a rural district of Hanoi, Vietnam. A total of 252 health workers (36 medical doctors and 216 nurses and technicians; 74% female) were interviewed. A job satisfaction measure was developed using factor analysis, from which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 19 publications
3
34
0
Order By: Relevance
“…This result is consistent with the finding from Vietnam [15]. Health professionals who were serving in the institution for ≥3 years were 2.83 times more likely got satisfaction with their job compared to< 3 years’ service.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with the finding from Vietnam [15]. Health professionals who were serving in the institution for ≥3 years were 2.83 times more likely got satisfaction with their job compared to< 3 years’ service.…”
Section: Discussionsupporting
confidence: 91%
“…In Vietnam among community health workers, age, areas of work and expertise, professional education, residence, sufficient number of staff were identified as factors affecting job satisfaction [15]. Hospital politics, personal relationships and the feeling of being able to provide a good quality of care also affects job satisfaction [10].…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, limited research has examined healthcare workers' job satisfaction, the findings suggest that job satisfaction is low because of insufficient salaries and benefits, poor facilities and equipment, and a lack of professional development opportunities (Tran, Van, & Hinh, 2013;Nguen, Duong, & Vu, 2016). These findings concur with the results of studies conducted in other developing countries such as Uganda (Luboga, Hagopian, Ndiku, Bancroft, & McQuide, 2011), Senegal (Rouleau, Fournier, Philibert, Mbengue, & Dumont, 2012), Tanzania (Mbaruku, Larson, Kimweri, & Kruk., 2014), Afghanistan, Malawi (Fogarty et al, 2014), and Ghana (Bonenberger, Aikins, Akweongo, & Wyss, 2014).…”
Section: Introductionsupporting
confidence: 70%
“…Particularly, stress, arising from handling severe illness and death, operating complex equipments, and experiencing a lack of recognition with members of other occupational groups or managers lead to burnout and job dissatisfaction [2, 6, 20]. A study done in Austria showed that one-quarter of anesthetists working in teaching hospitals were at risk for burnout syndrome (characterized by mental and physical exhaustion), and 50% of anesthetists had greater job dissatisfaction (P 0.002) with their job and plan to future dropout from their profession [21].…”
Section: Introductionmentioning
confidence: 99%